Perlindungan Tenaga Kerja Indonesia di Luar Negeri Melalui Sertifikasi Kompetensi - Ahmad Firdaus Sukomono (Faculty of Law, Maranatha Christian University, 2017)
With so many Indonesian Workers who work abroad showed that the government's ability to provide jobs is very limited. Statistical news 2016 states that the number of placement of Indonesian workers Abroad in 2016 amounted to 153. 804 with details of Indonesian manpower formal 82.443 Indonesian workers and informal 71.361 Indonesian workers. Comparing the two types of workers in the formal and informal sectors, the subject-matter of the author adopted is to provide protection to informal workers thus have a legal position that is better and stronger through a certificate of competence so as to protect the rights of workers and bargaining power balanced between giver employers and workers.Â Keywords: Legal Protection, Labor Indonesia, Certificate of Competency.